Analisis Kesulitan Siswa Dalam Memecahkan Masalah Dan Kemampuan Pemahaman Konsep Bangun Ruang Sisi Datar Pada Pembelajaran Jarak Jauh - Saepul Hidayat; Yanti Yanti; Aritsya Imswatama (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2022)
This study aims to determine the difficulties experienced by students in solving problems and understanding the concept of flat-sided geometry in distance learning. This research will use research with a qualitative approach. Through this qualitative research, it will encourage researchers to describe situations and conditions naturally in the form of narratives so that truthful information can be found about the analysis of students' difficulties in solving the problem of building a flat side space in distance learning. This research was conducted at SMP Al-Inayah with a sample of class VIII E, based on the results of the study in general the following data were obtained: (1) Distance learning has not been effective, (2) Students find it difficult to participate in distance learning due to technical and non-technical problems. technical, (3) limited face-to-face learning is used as a solution in learning.